Ӵук лысвуос: веросъёс / Егор Загребин - Загребин Егор Егорович (Удмуртия, 2022)
Экземпляры: (20230726) / Инвентарный номер: 65003 / Цена: 217.00 / Сис.шифр: С(удм) / Авт.знак: З-14 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Удм)